2010
DOI: 10.1002/cncr.25016
|View full text |Cite
|
Sign up to set email alerts
|

Age/race differences in HER2 testing and in incidence rates for breast cancer triple subtypes

Abstract: BACKGROUND: Although US year 2000 guidelines recommended characterizing breast cancers by human epidermal growth factor receptor 2 (HER2), national cancer registries do not collect HER2, rendering a population-based understanding of HER2 and clinical ''triple subtypes'' (estrogen receptor [ER] / progesterone receptor [PR] / HER2) largely unknown. We document the population-based prevalence of HER2 testing / status, triple subtypes and present the first report of subtype incidence rates. METHODS: Medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
82
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 38 publications
11
82
4
3
Order By: Relevance
“…TNBC is a more invasive cancer with higher degree of recurrence. About 14 to 20 percentages of breast cancers are triple negative (Carey et al, 2006;Hannemann et al, 2006;Lund et al, 2010). Similar to our study, the significant increase of the triple negative tumors with decrease of cancer onset age has been shown in many other studies in different countries that TNBC has been more frequent in younger ages (Dobi et al, 2011;Salami et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…TNBC is a more invasive cancer with higher degree of recurrence. About 14 to 20 percentages of breast cancers are triple negative (Carey et al, 2006;Hannemann et al, 2006;Lund et al, 2010). Similar to our study, the significant increase of the triple negative tumors with decrease of cancer onset age has been shown in many other studies in different countries that TNBC has been more frequent in younger ages (Dobi et al, 2011;Salami et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…This prevalence was higher than that reported in white patients (range, 10%-13%) but was closer to the prevalence reported in African-American patients (range, 23%-30%). 14,30 Few studies have been performed on Hispanics living in the United States. In a small study of 46 patients, the prevalence of TNBC was 10%, 14 although this low prevalence may not be representative because of the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2000 characterization of breast cancer, apart from expression of biomarkers for estrogen receptors (ER) and progesterone receptors (PR), has included also the human epidermal growth factor 2 (HER2) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have identified different subtypes of morphologically similar breast cancer patients with different prognosis and different therapeutic response through the evaluation of the combination of ER, PR and HER2 status, currently reported in routine pathology reports of breast cancer [1,5,6].…”
Section: Introductionmentioning
confidence: 99%